A Study On The Histopathological Analysis Of Nasal Masses Among Patients Attending The Ent Department Of Pakistan Institute Of Medical Sciences, Islamabad - Faisal, Malik Jawad; Arshad, Muhammad; Zafar, Moniba; Ashfaq, Ahmed Hasan; Shah, Syed Fahd (Journal of Rawalpindi Medical College, 2024)
Objective: The study was conducted to understand the different histopathological patterns, the classification of nasal tumours, and the relative distribution of the various lesions by age and sex. Method: In this study, 80 patients admitted to our hospital with nasal weights and numerous clinical presentations were selected. The study period is 2 years. This study was conducted in the Department of Otorhinolaryngology/ ENT and Histopathology department of the Pakistan Institute of Medical Sciences and AFIP for a two-year duration from April 2019 to April 2021. Results: The most numerous groups of changes were non-cancerous nasal growth; 55 cases (68.25%), then 25 cases (32.25%) of nasal tumours, 16 benign, and 9 malignant cases in cancerous tumours. Conclusion: Nasal obstruction and rhinorrhea are the most commonly encountered symptoms in our community, with simple inflammatory nasal polyps being the predominant histological pattern. Surgical intervention is considered the optimal treatment modality.